Optimizing Sound Speed Profiling for Hydrographic Surveys - Peyton, Derrick R.; Beaudoin, Jonathan; Lamplugh, Michael (The International Hydrographic Review, 2009)
The IHO Standards for Hydrographic Surveys (S-44) requires that hydrographic surveys account for sound speed uncertainties in order to determine the Total Propagated Uncertainty. If variations in sound speed are significant, the horizontal and vertical position of a sounding can vary by as much as several meters. Refraction artefacts can be typically dealt with in post-processing. This can be time consuming and require specialized processing expertise, especially in area of significant bathymetric relief and/or environmental variations in the water column. In this paper, we examine the application of recent advances in refraction based uncertainty to the ODIM Moving Vessel Profiler (MVP) controller software in order to optimize sound speed profiling operations.